The English Origins of Geotourism (as a Vehicle for Geoconservation) and Their Relevance to Current Studies - Thomas A. Hose (Acta Geographica Slovenica, 2011)
This paper contextualises the recognition of the geotourism concept. It stresses the underpinning geoconservation purpose that drove its development in England. It notes the multidisciplinary nature of geotourism research. It provides a summary of the development of early modern geoconservation in England as a necessary precursor to the inception, recognition and development of geotourism.  It notes the evolving geotourism research approach and its impact on its understandings, definitions and models; the whole is contextualised within the framework of special interest tourism. The interaction between geotourism and geoparks is considered. A new geotourism definition is provided and a plea made for its original rationale and observations to be included in studies elsewhere in Europe.